INITIAL STUDY OF OPTIMIZATION OF ALUMINIUM 1100 - ALUMINA POWDER (Al2O3) COMPOSITE PROCESSING WITH SCREEN PRINTING DISTRIBUTED ACCUMULATIVE ROLL BONDING METHOD TOWARD MECHANICAL PROPERTIES - Rachmantyo, Riska
Material technology growing to fulfills needs of industry on improving material properties more optimally and efficiently. One of them is a composite material technology with aluminium as matrix and alumina as reinforcement material. The process of metal matrix composites by casting method, generally will decrease the mechanical properties because the reinforcing material can not be distributed evenly throughout the composite part. In this research, the process composite of aluminium 1100 - alumina conducted by casting method, but it didn’t give significant results in mechanical properties. Oxide film which formed during casting on the aluminium surface also affects the mechanical properties. Oxide film forming prevention is carried out by flowing argon gas during casting process. The optimal result of tensile strength obtained at gas flow rate of 5 l/min is 89.77 ± 0.32 MPa. To further improve mechanical properties of the composite, the manufacturing process is tried by rolling method. Alumina was attached to the surface between 3 layers of aluminium plates, then heated to softening temperature before its melting point. The optimal process temperature occurs at 641-643 0C. The percentage of alumina as reinforcement is 1; 1.5; 2; 3; and 5%wt. The result give maximum strength at 5%wt of alumina, is 130.88 ± 1.12 MPa which is increased by 47% compared if composites were manufactured without alumina, and composite hardness was 72.33 ± 3.21 HRB or 151.84 ± 24.27 HV0,2. To obtain more optimal mechanical properties, the experiment using screen printed accumulative roll bonding method to distribute the alumina particle more evenly and have uniform distance and position. The more alumina used were give significant increase in strength and hardness. Maximum mechanical properties is occured when 5%wt alumina used. Maximum tensile strength obtained is 154.19 ± 2.39 MPa which is increased by 73% compared compared if composites were manufactured without alumina, and hardness is 90.33 ± 1.53 HRB or 180.93 ± 32.78 HV0.2. Further research is needed to get more optimal results.